1991
DOI: 10.1002/abio.370110416
|View full text |Cite
|
Sign up to set email alerts
|

Unusual wax esters and glycolipids: Biocatalytical formation and physico‐chemical characterization

Abstract: By aid of lipases, e.g. of Mucor miehei, in n-hexane wax esters were produced from usual primary fatty alcohols and unusual hydroxy fatty acids (in part of microbial origin). Thus, (S)-17-hydroxyoctadecanoic acid dodecyl ester and (Ri-3-hydroxy decanoic acid dodecyl ester were formed. I n measurements of the film pressure using a LANGiMUIR film balance the monolayers of both compounds indicated good stability compared to the non-hydroxy wax esters. Glycolipids de novo produced by microorganisms did not show su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…The catalytic activity of lipases toward hydroxy fatty acid esters was well studied by Hayes [2023]. In the esterification of several hydroxyl fatty acids Rhizomucor miehei lipase was also adopted [2427]. Steffen et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalytic activity of lipases toward hydroxy fatty acid esters was well studied by Hayes [2023]. In the esterification of several hydroxyl fatty acids Rhizomucor miehei lipase was also adopted [2427]. Steffen et al .…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic activity of lipases toward hydroxy fatty acid esters was well studied by Hayes [20][21][22][23]. In the esterification of several hydroxyl fatty acids Rhizomucor miehei lipase was also adopted [24][25][26][27]. Steffen et al used R. miehei and Candida antarctica lipases as biocatalyst for the synthesis of monoglycerides of 17-hydroxy-and 12-hydroxystearic acids with high yield [27].…”
Section: Introductionmentioning
confidence: 99%
“…Application of enzymes in various biochemical modifications of fats and oils is well established, and the catalytic activity of lipases toward hydroxy fatty acids is also well studied by various workers (3)(4)(5)(6)(7)(8)(9)(10)(11). According to this information, 1,2-specific lipases cannot act upon the hydroxyl group of HFA; this property has been taken advantage of in the esterification of HFA and alcohol so that estolide or lactone formation is avoided.…”
mentioning
confidence: 95%
“…Application of enzymes in various biochemical modifications of fats and oils with nonoxygenated fatty acids is well studied, but there is very few literature information regarding the use of enzymes in the modification of oils, which contain fatty acid with hydroxyl groups. Catalytic activity of lipases toward hydroxy fatty acids was studied by Hayes in his different publications [3][4][5] and also by Lang et al [6], Wagner et al [7], Steffen et al [8], and Bhattacharyya et al [9]. They all showed that lipases did not catalyze the esterification of the hydroxyl group of the fatty acid with alcohol so that estolide or lactone formation can be avoided.…”
mentioning
confidence: 99%